Sports injuries and emergencies : (McGraw-Hill, Health Professions Division, 2003)
A concise handbook of emergent care for sports injuries. Written for sports medicine physicians, internists, and family physicians who need immediate access to treatment information in the clinic, emergency department, training room, or on the sidelines. Emphasis is placed on emergency and sideline care along with return to play treatment. This necessary resource features a wealth of tables and illustrations as well as lists of emergency supplies needed in various sports.